Multicomponent synthesis of antibacterial dihydropyridin and dihydropyran embelin derivative - Peña, Rosalyn (2013)
A series of dihydropyran and dihydropyridin embelin derivatives were synthesized through a novel and straightforward, one pot protocol based on a three component reaction with embelin, aldehydes and cyclic enaminones as synthetic imputs. The type of substituent on the nitrogen atom of the β-enaminone is key to obtain nitrogenated or oxygenated rings. The obtained compounds were active against Gram-positive bacteria, including multiresistant Staphylococcus aureus clinical isolates